Insights into the terminal pleistocene climate of Australia from high resolution climate modelling - Andrew L. Lowry; Hamish A. McGowan (Scientific Reports)
Abstract Interpretations of the palaeoclimate at the end of the deglaciation over Australia suggest that conditions were becoming warmer, but there is an inconsistent picture of the monsoon and its impacts. This understanding can be improved using Earth System Models, but these are too coarse in resolution to fully interrogate the changes in the monsoon and associated climate experienced by early Aboriginal populations. Here we present the first downscaled climate modelling results at high resolution of Sahul–Australia in the terminal Pleistocene (12,000 years before present). The simulations were performed using the Weather Research and Forecasting (WRF) model downscaled from the Community Earth System Model (CESM) and compared to pre-industrial (1850 CE) simulations. Results show that the monsoon was active during this period, albeit in a less dominant form than the pre-industrial. Temperatures were generally 0.25–2 °C cooler than the pre-industrial in the south of Sahul and the eastern tropics, however over the central and western equatorial tropics of Sahul annual temperatures were 0.25–2 °C warmer, most notably in the austral spring. Aboriginal populations were generally stable until the onset of the Holocene, with populations retreating to refugia in times of unhospitable climatic conditions. Existing interpretations of these climates have insufficient spatial or temporal resolution to accurately describe the effects on Aboriginal populations. Here we quantify more precisely the changes in climate and identify the meteorological features that caused these changes, for example, the broadening of the monsoon trough, intensification of the Carpentaria heat low, meridional gradient of precipitation over the Lake Eyre Basin, and the zonal gradient of Tasmanian precipitation. These improvements in quantification of the palaeoclimate provides invaluable insight into the climate experienced by early Aboriginal populations in Sahul–Australia.